Pilot tests on methods to form working platform on soft clay - Sun, Liqiang (2018)
Pilot tests on the usage of vacuum preloading combined with short prefabricated vertical drains (PVDs) to form a working platform for future soil improvement work were conducted at a land reclamation site in Tianjin, China. The short PVDs were connected using three methods – the conventional vacuum preloading method, fish-bone connectors and embedded horizontal pipes. To investigate the influence of PVD spacing, short PVDs were installed in square grids with spacings of 0·4 m and 0·6 m. The ground surface settlement, pore water pressures, water content and undrained shear strength of the soil were measured during the specific period of vacuum preloading. The pilot tests indicated that short PVDs connected using embedded vacuum pipes installed at 0·4 m spacing were the most suitable method to form a working platform on the surface of the dredged marine clay. This method yields a substantial saving on construction cost and time while exhibiting similar efficiency to the conventional vacuum preloading method. The undrained shear strength and degree of consolidation of the soil after 60 d of vacuum preloading were 23·6 kPa and 85·1%, respectively, which met the requirements for the working platform.